Repeat Thoraco-Amniotic shunt placement to treat Fetal Pleural Effusion due to Pulmonary Sequestration - Sathyaprasad, Burjonrappa; Martin, Chavez (Journal of Fetal Surgery, 2017)
We report a twin gestation with one fetus afflicted by a left sided Extra-Lobar Sequestration (ELS) in a morbidly obese mother. The ELS was complicated by a left pleural effusion in the second trimester unresponsive to maternal steroid administration. We discuss the need for repeat shunt placement, in the setting of maternal morbid obesity and twin gestation. Shunt replacement was necessary secondary to dislodgement. Delivery at 34 weeks gestation was followed by successful surgical removal of the ELS. At one year follow up the infant has complete expansion of the left lung with no morbidity.
Keywords: Congenital Pulmonary airway malformation (CPAM); maternal steroid